Histomorphometric and transcriptomic features characterize silk glands' development during the molt to intermolt transition process in silkworm. (September 2016) - Hu, Wenbo; Liu, Chun; Cheng, Tingcai; Li, Wei; Wang, Niannian; Xia, Qingyou
Abstract: The molt–intermolt cycle is an essential feature in holometabolous and hemimetabolous insects' development. In the silkworm, silk glands are under dramatic morphological and functional changes with fibroin genes' transcription being repeatedly turned off and on during the molt–intermolt cycles. However, the molecular mechanisms controlling it are still unknown. Here, silk gland's histomorphology and transcriptome analysis were used to characterize changes in its structure and gene expression patterns from molt to intermolt stages. By using section staining and transmission electron microscope, a renewable cell damage was detected in the silk gland at the molt stage, and an increased number of autophagosomes and lysosomes were found in silk gland cells' cytoplasm. Next, by using RNA sequencing, 54, 578, 413 reads were obtained, of which 85% were mapped to the silkworm reference genome. The expression level analysis of silk protein genes and silk gland transcription factors revealed that fibroin heavy chain, fibroin light chain, P25/fhx, sericin1, sericin3 and Dimm had consistent alteration trends in temporal expression. In addition, differentially expressed genes (DEGs) were identified, and most of the DEGs associated with ecdysone signal transduction, mRNA degradation, protein proteolysis, and autophagy were significantly down-regulated in the transition from molt to intermolt, suggesting that these pathways were activated for the silk gland renewal. These findings provide insights into the molecular mechanisms of silk gland development and silk protein genes transcriptional regulation during the molt to intermolt transition process. Graphical abstract: Highlights: Silkworm silk gland was subjected to restorable cell damage during the molt to intermolt transition process. Formation of autophagosomes and lysosomes were observed in silk gland cells at the molt stage. Transcriptome profiling of the silk gland at the molt and intermolt stages were investigated. Genes of ecdysone signal transduction, mRNA degradation, protein proteolysis, and autophagy were activated at the molt stage. Model of silk gland renewal and silk protein synthesis during the molt to intermolt transition process was described.